2022
DOI: 10.1093/sleep/zsac137
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of pediatric narcolepsy following the 2009 H1N1 pandemic: a report from the pediatric working group of the sleep research network

Abstract: This study was aimed to evaluate yearly incidence of pediatric narcolepsy prior to and following the 2009 H1N1 pandemic and to evaluate seasonal patterns of narcolepsy onset and associations with H1N1 influenza infection in the United States. This was a multi-center retrospective study with prospective follow-up. Participants were recruited from members of the Pediatric Working Group of the Sleep Research Network including 22 sites across the United States. The main outcomes were monthly and yearly incident ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…17 Initial studies in the United States, which did not use the Pandemrix vaccine, showed no association with H1N1 influenza vaccine and narcolepsy, 18 whereas later multicenter studies found increased incidences of narcolepsy associated with both H1N1 vaccines and H1N1 circulating virus. 19 This back and forth of associations highlights the complexity of associating a rare neurologic disease with vaccinations with the risk of false attributions to the vaccine resulting in damaging consequences. The SARS-CoV-2 vaccines pose a similar challenge.…”
Section: Challenges In Determining Neurologic Complications Of Vaccinesmentioning
confidence: 99%
“…17 Initial studies in the United States, which did not use the Pandemrix vaccine, showed no association with H1N1 influenza vaccine and narcolepsy, 18 whereas later multicenter studies found increased incidences of narcolepsy associated with both H1N1 vaccines and H1N1 circulating virus. 19 This back and forth of associations highlights the complexity of associating a rare neurologic disease with vaccinations with the risk of false attributions to the vaccine resulting in damaging consequences. The SARS-CoV-2 vaccines pose a similar challenge.…”
Section: Challenges In Determining Neurologic Complications Of Vaccinesmentioning
confidence: 99%
“…In the United States and China, NT1 incidence rates were only weakly correlated to type A H1N1 influenza season severity 9,21 . This could be driven by geographic differences within these large countries in influenza season severity and strain dominance, or the influence of other, still unknown triggers.…”
Section: Introductionmentioning
confidence: 98%
“…Subsequent data from France suggested that the use of Pandemirix was associated with increased NT1 incidence rates in both children and adults 4 . Also in East Asia and the United States where Pandemrix was not used, incidence increases were noted, leading to the hypothesis that the type A H1N1 influenza virus itself may also trigger NT1 [5][6][7][8][9] . Later genetic evidence further supported this hypothesis 10 .…”
Section: Introductionmentioning
confidence: 99%